Teachers’ Attitude towards Inclusive Education: Latvian and Lithuanian Experiences - Dina Bethere; Romalda Kasiliauskiene; Linda Pavitola; Svetlana Usca (Social Sciences, 2023)
Inclusive education is a continuous process of transformation of the education system. It is both an approach to teaching and learning, as well as a different organization of the educational process that welcomes all students regardless of their social skills and physical and intellectual abilities. The qualitative implementation of inclusive education requires competent staff. The study reflects a comparative study carried out in Latvia and Lithuania, and it focuses on Latvian and Lithuanian teachers’ attitude self-assessment regarding the implementation of inclusive education. A three-dimensional model, including the cognitive, affective, and behaviour components, are used for the study. The Technical Manual for Attitudes Towards Teaching All Students Instrument developed by Gregory Jess L. and Noto Lori A. has been applied in the study. The SPSS 25.0 programme, Pearson Correlation, and One-Way ANOVA tests were used for the statistical analysis of the data. The results reveal, and generally confirm, differences in the structure of Latvian and Lithuanian teachers’ attitudes, as well as emphasize the importance of teachers and support specialists’ competence improvement to ensure optimal teaching and learning processes for all learners involved in the educational process.